1998
DOI: 10.1074/jbc.273.41.26739
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting cAMP Binding Domain A in the RIα Subunit of cAMP-dependent Protein Kinase

Abstract: The two gene-duplicated cAMP binding domains in the regulatory subunits of cAMP dependent protein kinase are each comprised of an A helix, an eight-stranded ␤-barrel, and a B and C helix (1). The A domain is required for high affinity binding to C, while the B domain regulates access to the A domain. Using a combination of a yeast two-hybrid screen coupled with deletion analysis, cAMP binding domain A of R I was dissected into two structurally and functionally distinct subsites, one that binds cAMP and another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…Most likely, these two residues are critically involved in the transmission of the signal from cAMP binding rather than in direct R-C interaction. Based upon studies using the yeast two-hybrid screening approach, Huang and Taylor (35) identified the sequence R I␣ 236 -244 (equivalent to R II␣ 240 -248 ) as an important contributor to C subunit binding, probably by direct C subunit interaction. In either model depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, these two residues are critically involved in the transmission of the signal from cAMP binding rather than in direct R-C interaction. Based upon studies using the yeast two-hybrid screening approach, Huang and Taylor (35) identified the sequence R I␣ 236 -244 (equivalent to R II␣ 240 -248 ) as an important contributor to C subunit binding, probably by direct C subunit interaction. In either model depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each domain has its own function and also communicates with other regions of the molecule as the holoenzyme undergoes conformational changes induced by cAMP binding (29). At the N terminus of the PKA-R subunit is a dimerization domain that functions to maintain the R-subunits as a stable dimer and provides a docking site for a variety of A kinase anchoring proteins (AKAPs), thereby localizing PKA to specific subcellular locations (43)(44)(45)(46)(47). After a variable, intervening linker domain at the C terminus of the PKA-R subunits are two tandem cAMP binding domains (A and B).…”
Section: Discussionmentioning
confidence: 99%
“…Two major interaction sites between the R and C subunits were defined previously (36,41,42). One is the autoinhibitory consensus site in the linker region of R that fills the active site cleft of the C subunit and competes for the substrate-binding site (41).…”
Section: Discussionmentioning
confidence: 99%